The Development of Augmented Reality Educational Media Using Think-Pair-Share Learning Model For Studying Buginese Language - Hasbi, Muhammad; Tolle, Herman; Supianto, Ahmad Afif (Faculty of Computer Science (FILKOM) Brawijaya University, 2020)
Language is a tool used for communication. Indonesia has a variety of languages, one of which is the Buginese language. As a language whose level of speakers exceeds five million, the popularity of this language begins to fade and is rarely used over the times. The Buginese language has its own letter called Lontara which consists of 23 letters. In addition to learning it difficult, educational media to learn this language, especially how to write letters is rarely developed. Learning this language is mandatory for formal school students ranging from elementary school to high school. However, a number of teachers noticed that Lontara writing lessons were very difficult for students to understand. Because of the difficulty level of writing, this research was conducted to answer and overcome these problems by developing an educational media called Lontara Augmented Reality. The research and development method (RnD) was utilized as the method in this study and it collaborates with ASSURE as the media development model. ASSURE model is used in the media design process. This media has an embedded learning model which called think-pair-share. The presence of this learninf model aims to enhance user skill in learning due to it provides learning with pair features. Educational media design has been validated by four media experts and four content materials validators. In the first iteration of validation, the average value of 3.90 was obtained with an average total score of 206.5 and a total percentage of around 78% (good category). After media being revised, an increase of 11% from the former iteration became 89% with 4.45 in average and total score of 235.75 (very good category). Furthermore, expert material content obtained an average value of 4.74 with a total average score of 99.5. with the percentage of the feasibility of the media reaching 95%. The percentage of usability testing results shows a great result with 96.91% in average and functionality tests around 100% which means that all of these functions this educational media application can work properly. in addition, performance testing and compatibility results show a normal activities. Memory and CPU usage are in normal conditions and not disturbing the applicaton performance. Lontara Augmented reality compatible in many android smartphones. Around 15 types of devices have been installed and it can run normally in these devices.